Analysis of risk factors and construction of a predictive model for contralateral occult carcinoma in patients with unilateral papillary thyroid carcinoma - Zhao, ShiYi; Yan, Wei; Yu, Jin; Chen, DeJie (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the risk factors associated with contralateral occult carcinoma in patients with unilateral papillary thyroid carcinoma and to develop a corresponding prediction model to enhance early detection and clinical management of occult carcinoma.MethodsThe clinical data of 430 patients who underwent total thyroidectomy for unilateral papillary thyroid carcinoma at Xiangyang Central Hospital between January 2021 and December 2022 were collected. Univariate and multivariate logistic regression analyses were performed to identify risk factors for contralateral occult cancer in patients with unilateral thyroid carcinoma. A prediction model was established, and the diagnostic value of the model was assessed using calibration curves and decision curve analysis.ResultsThe results of univariate logistic regression analysis indicated that tumor diameter, tumor location, multifocality, presence of contralateral benign nodules, and lateral neck lymph node metastasis were risk factors for contralateral occult carcinoma in patients with unilateral thyroid cancer (P < 0.05). Multivariate logistic regression analysis further showed that a tumor diameter >1 cm, proximity of the tumor to the isthmus, multifocality, presence of contralateral benign nodules, and lateral neck lymph node metastasis were independent risk factors for contralateral occult carcinoma in unilateral thyroid cancer (P < 0.01). A risk nomogram model was developed based on these five risk factors, with areas under the curve (AUC) of 0.921 and 0.96 for the training and validation sets, respectively. The calibration curve demonstrated good consistency, and decision curve analysis indicated that the model had a high level of net benefit.ConclusionA tumor diameter >1 cm, proximity of the tumor to the isthmus, lateral neck lymph node metastasis, presence of contralateral benign nodules, and multifocality are independent risk factors for contralateral occult carcinoma in patients with unilateral papillary thyroid carcinoma. The predictive model developed in this study demonstrates strong predictive ability for the occurrence of contralateral occult carcinoma in patients with unilateral papillary thyroid carcinoma.